Neural-Guided RANSAC for estimating epipolar geometry [data] - Brachmann, Eric (Universität, 2020)
Pre-computed sparse feature correspondences for pairs of images (outdoor and indoor) to reproduce the experiments described in our paper, particularly to train and evaluate NG-RANSAC. For more information, also see the code documentation: https://github.com/vislearn/ngransac
Production date: 2019-03-31
Gesehen am 14.09.2020
Keywords: Forschungsdaten; Datenbank